The significance of 2-furyl ring substitution with a 2-(para-substituted) aryl group in a new series of pyrazolo-triazolo-pyrimidines as potent and highly selective hA3 adenosine receptors antagonists: new insights into structure-affinity relationship and receptor-antagonist recognition - Cheong, S.; Dolzhenko, A.; Kachler, S.; Paoletta, S.; Federico, S.; Cacciari, B.; Dolzhenko, Anton; Klotz, K.; Moro, S.; Spalluto, G.; Pastorin, G. (ACS Publications, 2010)
Among the heterocyclic structures identified as potent human A3 (hA3) adenosine receptor’s antagonists, we have demonstrated that the new pyrazolo-triazolo-pyrimidines, bearing an aryl group in replacement of the C2-furyl ring, not only confer a good pharmacological profile (with significantly enhanced selectivity against other adenosine receptor subytpes) but also overcome the metabolic transformation of the furan ring into toxic intermediates. All the synthesized [2-(para-substituted) phenyl]-pyrazolo-triazolo-pyrimidines showed affinity at the hA3 receptor in the low nanomolar range. The most potent derivative of the series presented better affinity and excellent selectivity (compound 31, Ki hA3 = 0.108 nM; hA1/hA3 = 5200; hA2A/hA3 = 7200), in comparison to the C2-furyl counterpart. A receptor-driven molecular modeling investigation, based on a recently proposed model of A3 receptor derived from the crystallographic structure of human A2A receptor, has been carried out in order to support the experimental binding data and to justify the enhanced selectivity against the other receptor subtypes